2012
DOI: 10.1210/jc.2012-2570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Levothyroxine on Bone Mineral Density, Muscle Force, and Bone Turnover Markers: A Cohort Study

Abstract: There was little evidence of adverse LT(4) effects on bone; however, premenopausal women with DTC might be at risk for reduced vBMD in their ultradistal radii.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 87 publications
2
33
0
Order By: Relevance
“…A systematic review of 21 studies of the effect of L-T4 therapy on BMD found that post-menopausal women with subclinical hyperthyroidism are at higher risk for developing osteoporosis, while men and premenopausal women are not [10]. Concordantly, overall adverse effect of L-T4 was not found in a recent study, yet peri-menopausal women with DTC might be at risk for reduced BMD at ultradistal radii also confirmed by the higher level of bone resorption marker (C-terminal telopeptide of type 1 collagen) as compared with controls [12]. A prospective study also demonstrated that TSH suppression after surgery for papillary thyroid carcinoma had adverse effects on BMD in women aged above 50 years but not in younger patients [14].…”
Section: Proximal Femurmentioning
confidence: 85%
See 1 more Smart Citation
“…A systematic review of 21 studies of the effect of L-T4 therapy on BMD found that post-menopausal women with subclinical hyperthyroidism are at higher risk for developing osteoporosis, while men and premenopausal women are not [10]. Concordantly, overall adverse effect of L-T4 was not found in a recent study, yet peri-menopausal women with DTC might be at risk for reduced BMD at ultradistal radii also confirmed by the higher level of bone resorption marker (C-terminal telopeptide of type 1 collagen) as compared with controls [12]. A prospective study also demonstrated that TSH suppression after surgery for papillary thyroid carcinoma had adverse effects on BMD in women aged above 50 years but not in younger patients [14].…”
Section: Proximal Femurmentioning
confidence: 85%
“…Overt hyperthyroidism is associated with an increased risk of osteoporosis, while whether subclinical hyperthyroidism affects the skeleton is under debate [7,8]. Effects of the latter on bone mineral density (BMD) have been addressed in a number of studies with somewhat controversial results [9][10][11][12][13][14][15]. The current understanding is that subclinical hyperthyroidism is a risk factor for osteoporosis in postmenopausal women but not in premenopausal women or male patients [10].…”
mentioning
confidence: 99%
“…DTC patients who do not achieve CR are generally treated with TSH suppressive therapy, which in the long term is associated with, among others, undesired cardiovascular side effects [16][17][18][19] and a possible reduction of bone mass [20,21]. However, once CR is reached, TSH levels in the lower half of the normal range can be restored [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Postmenopausal women with DTC may suffer from bone loss [53,61,62,63], while THST does not - or to a much lesser extent - affect BMD in premenopausal women and men [64,65]. Of female DTC patients randomized to THST (but not those randomized to a TSH in the normal range), patients of 50 years and older had a significantly decreased BMD within 1 year, which was not applicable to those under 50 years of age [61].…”
Section: Thyroid Hormone Suppression Therapymentioning
confidence: 99%